Survival Outcomes in Invasive Candidiasis: Exploring the Role of Chronic Disease Prevention and Healthy Lifestyle in Malaysia - Nordin, Syazwan; Hairon, Suhaily Mohd; Than, Leslie; Lee, Low Lee; Hadi, Siti Rohani Abdul; Sukeri, Surianti (Universitas Prima Indonesia, 2025)
Invasive candidiasis (IC) is a life-threatening fungal infection, particularly prevalent among patients with non-communicable diseases (NCDs). The rising incidence of NCDs in Malaysia poses a significant challenge to IC management and patient survival. Objective of this study was to determine the median survival time of IC patients in Malaysia and explore the relationship between survival outcomes, chronic disease prevention. This retrospective cohort study analyzed data from 445 patients diagnosed with IC at a tertiary hospital in Malaysia. Data on sociodemographics, comorbidities, clinical presentation, Candida species, treatment and patients outcome were collected and analysed using Kaplan-Meier survival estimates. The median survival time for IC patients was 21 days, with significant variations based on age, ethnicity, and comorbidities. Patients with diabetes on insulin therapy exhibited a lower mortality risk, likely due to better glycemic control and higher health-seeking behavior. Candida parapsilosis infections were associated with higher survival rates, while Candida glabrata and Candida tropicalis infections were linked to poorer outcomes. These findings highlight the importance of tailored treatment strategies that consider patient comorbidities and the specific Candida species involved. Integrating preventive measures for NCDs and promoting healthy lifestyle practices are crucial for improving IC patient survival